تقييم واقع المراجعة الداخلية في المؤسسات الإقتصادية من منظور المعايير الدولية - بوعزيز إبراهيم (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجاريةوعلوم التسيير, 2018)
لملخص باللغة العربية تهدف هذه الدراسة إلى تقييم واقع الممارسات المهنية للمراجعة الداخلية في المؤسسات الاقتصادية الجزائرية من خلال تحديد درجة توافقها مع المعايير الدولية للمراجعة الداخلية المنبثقة عن معهد المراجعين الداخليين الأمريكي. ولتحقيق أهداف الدراسة واختبار الفرضيات، تم القيام بدراسة ميدانية تتضمن دراسة حالة إحدى المؤسسات الاقتصادية الجزائرية (مؤسسة إسمنت حجار السود)، بالإضافة إلى إعداد استبيان يتضمن مجموعة من الأسئلة تعالج موضوع الدراسة وتحليل النتائج عن طريق استخدام برنامج الرزمة الإحصائية للعلوم الاجتماعية SPSS. حيث وزعت ثمانون (80) استبياناً على المراجعين الداخليين لعينة من المؤسسات الاقتصادية الجزائرية، وتم استرجاع خمسة وسبعين (75) منها، تسعة وستون (69) قابلة للاستعمال. وخلصت هذه الدراسة إلى أن ممارسة المراجعة الداخلية في المؤسسات الجزائرية محل الدراسة تتوافق إلى حد كبير مع المعايير الدولية للمراجعة الداخلية المتعلقة بمعايير الأداء، وجزئياً مع معايير الصفات. كما تستحوذ مهام المراجعة المالية ومراجعة التطابق على النصيب الأكبر من المهام التأكيدية التي يتم إنجازها، يقابلها غياب كلي للخدمات الاستشارية لإدارة المؤسسة، إلا أن المراجعين الداخليين في المؤسسات الجزائرية لديهم كفاءة مهنية ومهارات مقبولة تسمح لهم بالقيام بأعمالهم على أحسن وجه. وقد أوصت هذه الدراسة بضرورة إصدار معايير مراجعة داخلية تتلاءم وبيئة الجزائر، تكون مستمدة من المعايير الدولية المنبثقة عن المعهد الأمريكي، بالإضافة إلى نشر ثقافة المراجعة الداخلية الحديثة وفق المقاربة بالأخطار بالمؤسسات الاقتصادية الجزائرية، والعمل على ضرورة الاهتمام أكثر بتكوين الكفاءات البشرية الملائمة لاحتياجات هذه الوظيفة، من خلال تنظيم ملتقيات حول التطورات والمستجدات في المجال المتعلق بالمراجعة، والحرص على توفير البيئة التنظيمية الملائمة لأداء دورها بفعالية عالية. الكلمات المفتاحية: معايير المراجعة الداخلية، إدارة المخاطر، الرقابة الداخلية، الحوكمة.Abstract This study aims to evaluate the reality of the professional practices of internal auditing in the Algerian economic institutions through determining its degree of consistency with the international standards that emanating from the American Institute .However, To achieve the objectives of this study and test its hypotheses we did a field Study which contains the case study of one of the Algerian economic institutions (the Black Stone Cement Corporation).Besides, the preparation of a questionnaire that includes a set of questions that deal with the subject of the study and analysis of the results by using the SPSS program, whereas Eighty (80) questionnaires distributed to the internal auditors of a sample of Algerian economic institutions which were retrieving seventy-five (75) but sixty-nine (69) usable. The study concluded that the internal audit practice in the Algerian institutions under study is largely in line with the International Standards for Internal Auditing on performance standards, but there is a partial in conformity with standards of attributes. The functions of financial and conformity auditing capture the largest share of the assurance tasks to be completed, in the other side the absence of all consultancy services for the management of the institution, but the internal auditors in Algerian institutions have professional competence and acceptable skills that allow them to do their work best. This study recommended that there is necessary to issue internal auditing standards appropriate to the environment of Algeria, which should be derived from the international standards emanating from the American Institute, in addition to spreading the culture of modern internal auditing according to the approach of risk in the Algerian economic institutions, and working on the need to pay more attention to the formation of human competencies appropriate to the needs of this function, Through organizing meetings on developments and latest information in the field of auditing, and ensuring to provide of an appropriate regulatory environment in order to perform its role effectively. Keywords: Internal Audit Standards, Risk Management, Internal Control, Governance
دراسة حالة عينة من المؤسسات الإقتصادية الجزائرية
Keywords: معايير المراجعة الداخلية; إدارة المخاطر; الرقابة الداخلية; الحوكمة; المراجعة الداخلية في المؤسسات الإقتصادية; المعايير الدولية; المؤسسات الإقتصادية الجزائرية